Caesarean section rate and its determinants in a rural area of South India - N., Divyamol; Raphael, Lucy; Koshy, Nileena (International Journal Of Community Medicine And Public Health, 2016)
Background: The world is currently witnessing an increase in the rate of caesarean sections which can be ascribed to many factors including socio-demographic factors and personal preferences apart from the clinical indications. This study is done to assess the rate of caesarean section in rural Kerala of South India and to determine the factors associated. Methods: A community based cross sectional study using a pretested semi-structured questionnaire was conducted among mothers who delivered between April 2011- march 2012 in a rural area of Thrissur district in Kerala, South India. Analysis was done using SPSS16. Results: Rate of caesarean section is 37.7%. The major indications were previous caesarean sections (40.44%), failure of labor to progress (22.47%) and fetal distress (14.6%). Univariate analysis showed significant association between caesarean section and higher educational status of the women and husband, higher occupational status of the women and husband, and undergoing ultrasonography >3 times in the antenatal period. On multivariate analysis higher occupational status of women (OR [CI] =3.35 [1.03-10.8]), multiparity (OR [CI] =1.96 [1.05-3.6]), and >3 ultrasonograms (OR [CI] =2.05 [1.08-3.89]) were found to be significant risk factors. Conclusions: Rate of caesarean section in present study is above the expected levels. Study brings out association of woman’s occupation, parity and number of ultrasonography with caesarean sections. It is important to make the public aware regarding the benefits of natural births. Government level policies supporting normal deliveries should be advocated.